PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA DI SDN TIDUNG KELAS II MENGGUNAKAN MODEL PEMBELAJARAN DIRECT INTRUCTION BERBANTUAN MEDIA KARTU BERGAMBAR - Nirwana S; Abd Munir Kondongan; Haslinda (STKIP Subang, 2025)
Nirwana S. 2025. Improving Students’ Beginning Reading Skills in Grade II of SDN Tidung Using the Direct Instruction Learning Model Assisted by FlashCards. Thesis. Elementary School Teacher Education Department, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor 1 Abd Munir Kondongan and Haslinda. The main problem in this study is that students’ initial reading ability is still classified as low. This study aims to describe the improvement in the initial reading ability of second-grade students at Tidung Elementary School using the Direct Instruction learning model assisted by picture cards. This type of research is Class Action Research which consists of two cycles, each cycle is carried out in two meetings. The research procedures include planning, implementation of actions, observation and reflection. The subjects in this study were 20 students of grade II of SDN Tidung, Rappocini District, Makassar City. The collected data were analyzed using quantitative and qualitative analysis.The results of this study indicate that there was an increase in student learning activities from cycle I to cycle II, student learning outcomes increased with an average score difference of 16, the average score of student learning outcomes in cycle I was 64 increasing to 80 in cycle II. Students’ initial reading learning completeness also increased by 45%, in cycle I which was completed individually out of 20 students only 11 (55%) students achieved learning completeness (KKM) and classical learning completeness had not been achieved. While in cycle II of 20 students there were 20 (100%) students who had achieved learning completeness (KKM) and classical learning completeness was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed was more than 80%.Based on the results of the research above, it can be concluded that the initial reading ability of class II students of Tidung Elementary School, Rappocini District, Makassar City through the application of the direct instruction learning model assisted by picture card media has increased.